Representasi komunitas Asia di Prancis pada gerakan anti rasisme Je Ne Suis Pas Un Virus dalam media daring Le Figaro - Dino, Awan; Ratna; Savitri, Dian (Franconesia, 2022)
This research aims to explain the representation built by the author of Le Figaro news article in this discourse towards the Asian community in France with structures according to Teun Van Dijk. This descriptive qualitative research was conducted to find out and obtain the structures of critical discourse from the perspective of Teun A van Dijk in the online media Le Figaro with the study of critical discourse analysis. The data sources used are news articles published by Margaux d'Adhémar from Le Figaro online media in January 2020. The objects of this research are words, phrases, clauses, and sentences contained in the article. The data collection technique of this research comes from documentation study research. The data analysis technique used is van Dijk's critical discourse analysis study model which includes three structures, namely the text dimension, social cognition, and social context. If analysed in general, the news writer wants to convey a message about the social problems that befall some Asian communities in France after the emergence of the Covid-19 case in France. These problems are racist acts that occur to the Asian community in France. So that this incident is the background for the emergence of the anti-racism movement "Je Ne Suis Pas Un Virus". Through the discourse strategy model of Teun A van Dijk, this research found that the information in each sentence contained in the text is related to the next information sentence. This study also found that the text of this news article is one of the representations of the social conditions of the Asian community in France who experience racist acts.